Therapeutic and Diagnostic Translation of Extracellular Vesicles in Cardiovascular Diseases: Roadmap to the Clinic. Issue 14 (6th April 2021) - Sahoo, Susmita; Adamiak, Marta; Mathiyalagan, Prabhu; Kenneweg, Franziska; Kafert-Kasting, Sabine; Thum, Thomas
Abstract : Exosomes are small membrane-bound vesicles of endocytic origin that are actively secreted. The potential of exosomes as effective communicators of biological signaling in myocardial function has previously been investigated, and a recent explosion in exosome research not only underscores their significance in cardiac physiology and pathology, but also draws attention to methodological limitations of studying these extracellular vesicles. In this review, we discuss recent advances and challenges in exosome research with an emphasis on scientific innovations in isolation, identification, and characterization methodologies, and we provide a comprehensive summary of web-based resources available in the field. Importantly, we focus on the biology and function of exosomes, highlighting their fundamental role in cardiovascular pathophysiology to further support potential applications of exosomes as biomarkers and therapeutics for cardiovascular diseases.